Pengaruh Terpaan Berita Online Kompas.com dan E-WOM di Media Sosial pada Kasus Ledakan Depo Pertamina Plumpang terhadap PT Pertamina (Persero) - Khansa, Devani; Hanika, Ita (Jurnal Mahardika Adiwidia, 2024)
In the rapidly evolving digital communication, the dynamics of online news consumption and electronic word of mouth (eWOM) have become integral components influencing public perceptions of corporate entities. This research seeks to explain the relationship between online news exposure of Kompas.com, electronic word of mouth, and their influence on the company reputation of PT Pertamina (Persero). This research uses a quantitative methodology, utilizing the cluster random sampling technique to ensure a representative sample. A structured questionnaire distributed to 185 respondents living in six sub-districts of North Jakarta. With the framework of Agenda Setting Theory, this research explores how online news exposure and electronic word of mouth collectively contribute to shaping the public agenda, thereby influencing perceptions of company reputation. The Agenda Setting Theory provides a theoretical view through which to analyze the process by which certain issues gain prominence in the public sphere, guiding our investigation into the dynamics of online news and eWOM on corporate reputation. The results of this research show: 1) Exposure to Kompas.com online news has a significant effect on the reputation of PT Pertamina (Persero) with a regression coefficient value of 0.281; 2) Electronic word of mouth has a significant effect on the reputation of PT Pertamina (Persero) with a regression coefficient value of 0.230; 3) Simultaneous exposure to online news and E-WOM has a significant effect on the reputation of PT Pertamina (Persero) with a Sig value. 0,000.